2023
DOI: 10.1177/02653788231161338
|View full text |Cite
|
Sign up to set email alerts
|

Muslim Diasporas: An Examination of the Issues of the Second and Third Generation Muslims in Europe

Abstract: This article studies the issues of the emerging second and third generations of post-war Muslim migrants in Europe. There has always been some presence of Muslims in Europe, but immigrants who came in the post-Second World War (WWII) period represent the majority of today's Muslim diasporas in Europe. They are referred to as the ‘first generation’. This division is made to distinguish between those who had moved permanently to a country other than their country of birth, from the second/third-generation immigr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Previous studies showed that many violent extremists in Europe belong to the second-generation of Muslim immigrants [29,30]. They often seek a balance between their newly adopted practical European lifestyle and the cultural heritage they received from their parents [31,32]. These individuals carry the weight of their ethnic and religious backgrounds while also feeling compelled to navigate between different identities to maintain family connections while integrating into European society [31,32].…”
Section: Development Of Violent Extremist Behavior In Radicalization ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies showed that many violent extremists in Europe belong to the second-generation of Muslim immigrants [29,30]. They often seek a balance between their newly adopted practical European lifestyle and the cultural heritage they received from their parents [31,32]. These individuals carry the weight of their ethnic and religious backgrounds while also feeling compelled to navigate between different identities to maintain family connections while integrating into European society [31,32].…”
Section: Development Of Violent Extremist Behavior In Radicalization ...mentioning
confidence: 99%
“…They often seek a balance between their newly adopted practical European lifestyle and the cultural heritage they received from their parents [31,32]. These individuals carry the weight of their ethnic and religious backgrounds while also feeling compelled to navigate between different identities to maintain family connections while integrating into European society [31,32]. Identity uncertainty and identity fusion are associated with quests for meaning in life.…”
Section: Development Of Violent Extremist Behavior In Radicalization ...mentioning
confidence: 99%
See 1 more Smart Citation